BIMBINGAN PELAKSANAAN IBADAH QURBAN BAGI PESERTA DAN PANITIA DI LINGKUNGAN MASJID AL-JIHAD 1446 H. 2025 M. DESA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Hasan Hasan (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
Qurban is an act of worship performed continuously by the Muslim community; the process is similar to the Hajj. Every Muslim who has money slaughters Qurban animals almost every year, either individually or in groups, organized by the general public, private institutions, and the government. In Islam, Qurban is a very important way to show devotion to Allah. The formulation of the problem in this service, is “Why does the implementation of Qurban always bring up problems that continue to recur every year?” While the purpose of this service is to “carry out guidance and equalize views among participants and Qurban committees in the Al-Jihad Mosque environment”. In implementing this counseling guidance, using a qualitative descriptive method, the subject of this service is Guidance on the Implementation of Qurban Worship for Participants and Committees in the Al-Jihad Mosque Environment 1446 H. / 2025 AD. Kubang Jaya Village, Siakhulu District, Kampar Regency, Riau Province. The results of the guidance are as follows: 1. Qurban participants and worshipers in general still do not understand in detail about the procedures for implementing Qurban worship. 2. The tendency of the committee members to still expect wages from meat in return for their work to help the process of implementing the Qurban worship. 2. There are still many assumptions in the community that non-Muslims should not be given Qurban meat.